Appropriative practices and the ontology of economic form - Dave Elder-Vass (2020)
Despite their differences, both mainstream economics and Marxist political economy see the contemporary economy as a thoroughly capitalist market system. This leads both to ignore large areas of the economy and thus to obscure the widespread presence of other economic forms. This has become both more significant and more obvious with the profusion of novel economic forms in the growing digital economy, including gift forms and gift-commodity hybrids. In response, this paper proposes a new framework for analysing diverse economic systems: an ontology of economic forms in which each form is a complex of appropriative practices. Different economic forms are structured by different combinations of practices, and we can explain how each form operates by analysing the practices involved and the tendencies generated by their interaction. The argument is illustrated by applying it briefly to some sample cases from the contemporary digital economy: Wikipedia, Apple, and Google’s web search service. The paper may also be read as an application of critical realism to an empirical case and thus as an illustration of some of the issues that arise when we seek to apply the realist framework in social research.